2017
DOI: 10.1093/jme/tjx086
|View full text |Cite
|
Sign up to set email alerts
|

First Record of Lutzomyia (Lutzomyia) longipalpis (Diptera: Psychodidae: Phlebotominae) on the Trinational Frontier (Brazil–Peru–Bolivia) of South-Western Amazonia

Abstract: In South America, the main sand fly species involved in the transmission of Leishmania infantum chagasi (Cunha & Chagas, 1937), etiological agent of the visceral leishmaniasis (VL), is Lutzomyia longipalpis (Lutz & Neiva, 1912). The species has been recorded in Colombia, Venezuela, Bolivia, Argentina, Paraguay, Uruguay, and Brazil, where it is recorded in 24 of the 27 Brazilian states, except Acre, Amazonas, and Santa Catarina. Collections were carried out for one year (April 2013 to March 2014) using modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…(2) There are no records of human cases of visceral leishmaniasis (VL) in Acre; nevertheless, there is a need for constant monitoring of the phlebotomine fauna and domestic animals, particularly dogs, since the occurrence of Lutzomyia longipalpis, the main vector of Leishmania (Leishmania) infantum in Brazil, has been recorded in the municipality of Assis Brasil (Acre) and in Bolivia and Peru. (8) Brasiléia is located on the border with Cobija municipality (District of Pando -Bolivia); are highly dependent on commercial activities and represent areas of high endemicity for CL, with great circulation of people between these cities. The present study aims to describe the sandfly fauna found in the municipality of Brasiléia and to evaluate the Leishmania DNA-detection index, followed by the molecular characterisation of the parasite species and, in parallel, the identification of blood meal sources in the captured insects.…”
mentioning
confidence: 99%
“…(2) There are no records of human cases of visceral leishmaniasis (VL) in Acre; nevertheless, there is a need for constant monitoring of the phlebotomine fauna and domestic animals, particularly dogs, since the occurrence of Lutzomyia longipalpis, the main vector of Leishmania (Leishmania) infantum in Brazil, has been recorded in the municipality of Assis Brasil (Acre) and in Bolivia and Peru. (8) Brasiléia is located on the border with Cobija municipality (District of Pando -Bolivia); are highly dependent on commercial activities and represent areas of high endemicity for CL, with great circulation of people between these cities. The present study aims to describe the sandfly fauna found in the municipality of Brasiléia and to evaluate the Leishmania DNA-detection index, followed by the molecular characterisation of the parasite species and, in parallel, the identification of blood meal sources in the captured insects.…”
mentioning
confidence: 99%
“…In 2017, Lu. longipalpis presence was recorded in Assis town, Acre state, tri-national border Brazil, Bolivia, and Peru 21 . In 2018, specimens were found in Yacuiba and Tarija (Magne M., pers.com).…”
Section: Vectorsmentioning
confidence: 95%
“…Sandflies are responsible for the transmission of Leishmania in the Americas, where the main vector species responsible to transmit the etiologic agent for visceral leishmaniasis (VL), Leishmania infantum , is Lutzomyia longipalpis . Despite recent VL cases in Santa Catarina State, L. longipalpis was not found, thus far (Borges et al, 2017). Other sandfly species such as Nyssomyia neivai have been collected in this state and have been detected with L. infantum DNA when evaluated by molecular techniques (Saraiva et al, 2009; Grott et al, 2015).…”
Section: Introductionmentioning
confidence: 94%